UTILIZATION OF SECONDARY TRICTICALE PROCESSING PRODUCTS WITH PRODUCTION OF FODDER MICROBIAL-VEGETATIVE CONCENTRATE FOR POND FISH - Nikolay R. Andreev; Valentina V. Kolpakova; Vladimir G. Goldstein; Irina K. Kravchenko; Ruzaliya V. Ulanova; Valentina A. Gulakova; Lyudmila V. Shevyakova; Mariya A. Makarenko; Nikolai D. Lukin (Юг России: экология, развитие, 2017)
Abstract. Aim. The aim of the study was to develop a process for the utilization of secondary products of triticale grain processing into starch and protein concentrate with production of fodder microbial-vegetative concentrate (FMVC) for pond fish. Methods. Standard and special methods for the analysis of chemical, biochemical composition (amino acid, mineral, fatty acid, carbohydrate), microbiological parameters of triticale grain, secondary products of its processing and FMVC were used in this work. Results. It is shown that considering the peculiarities of the chemical composition of whey water, insoluble residue and pulp, it is expedient to produce FMVC by bioconversion method using the producer-yeast Saccharomyces cerevisiae. The feed value of FMVC in terms of protein, lipids, minerals, and fiber met the normative parameters for fodder for pond fish of the Cyprinidae family. FMVC contained digestible carbohydrates, a high-quality protein with essential amino acids and lipids, which included saturated, unsaturated fatty acids, including ω-6, ω-3 families and phosphatides. Conclusion. A process of bioconversion has been developed for the utilization of secondary products of triticale grain processing into starch A and protein concentrate, with the production of FMVC for pond fish based on whey waters. The concentrate was characterized by high values of essential amino acids score, the predominance of unsaturated fatty acids, the presence of biologically active phospholipids, sterols, micro-, macroelements. The use of a concentrate as an additive will ensure the survivability of fish, increase growth, reduce the cost of feed and improve the ecological situation of the starch factory.